Socio-economic assessment of wheat variety Shatabdi in some selected areas of Bangladesh - Baksh, M Elahi; Kabir, Md Jahangir; Kispatta, Kalpona (Bangladesh Journal of Agricultural Research, 2010)
The survey was conducted in two villages under Dinajpur and Thakurgaon Districts during March 2004 to assess the socioeconomic aspects of Shatabdi wheat variety adoption at farm level. Stratified random sampling technique was followed for farmer selection. All categories of farmers expected wheat varieties having high yielding potentialities with less disease and pest infestation, more heat tolerant, and bold grain with golden colour. New wheat variety Shatabdi is able to meet the maximum expected characters. Old variety Kanchan was more disease susceptible and new one was free from disease. A significant yield difference was found between new and old verities (Shatabdi yielded 3l% to 43% higher compared to Kanchan over the locations and farmers group). Gross margin (return over variable cost) of Shatabdi also higher compared to Kanchan. By cultivating new variety, farmers earned additional gross margin of Tk. 6446 to Tk. 8353 per hectare in Jagdal and Tk. 6097 to Tk. 9314 per hectare in Daulatpur over Kanchan. Cent percent farmers over the locations said that their income was increased by cultivating Shatabdi compared to old variety Kanchan. The non-adopter farmers wanted new variety seeds. All groups of farmers wanted training/video show for up-dating their technical know how. Key Words: New vs old varieties; profitability level; farmers' adoption. DOI: 10.3329/bjar.v34i2.5792 Bangladesh J. Agril. Res. 34(2): 215-226, June 2009